CPU socket
The CPU socket, made from a liquid crystal polyester resin composition with controlled fibrous filler distribution and plate-like fillers, addresses the issues of cracking and torsion resistance in narrow pitch sockets, achieving superior metal fitting and molding stability.
Patent Information
- Application Number
- JP2024153917
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-04-18
- Filing Date
- 2024-09-06
- Publication Date
- 2025-05-02
AI Technical Summary
Existing CPU sockets with narrow pitch spacing suffer from cracks due to metal terminal insertion, reduced yield, and high residual stress from excessive orientation of liquid crystal polyester resin during injection molding, leading to poor torsion resistance and molding stability.
A CPU socket formed from a liquid crystal polyester resin composition containing 60 to 200 parts by weight of fibrous filler per 100 parts by weight of resin, with controlled fiber length distribution and inclusion of plate-like fillers, to enhance metal fitting properties and torsion resistance during high-temperature and high-pressure molding.
The proposed CPU socket exhibits excellent metal fitting properties and torsion resistance, even at narrow pitch intervals, and maintains stability under harsh molding conditions, improving manufacturing yield and product reliability.
Smart Images

Figure 2025070973000013 
Figure 2025070973000014 
Figure 2025070973000015
Abstract
Description
[Technical field]
[0001] The present invention relates to a CPU socket, and more particularly to a CPU socket obtained by using a liquid crystal polyester resin composition. [Background technology]
[0002] Liquid crystal polyester resins have excellent heat resistance, fluidity, and dimensional stability, and are therefore used in electrical and electronic components that require these properties. In particular, with the increasing performance of devices in recent years, there is an increasing need for molded products with thin walls and complex shapes, such as CPU (central processing unit) sockets.
[0003] A CPU socket is a connection terminal for an IC chip provided on a main board (motherboard) inside a computer, and the shape of the CPU socket is becoming more complex in response to the increasingly complex shapes of CPUs. As materials for conventional planar connectors such as CPU sockets, planar connectors have been proposed that are molded from composite resin compositions containing a plate-like filler such as a liquid crystal polymer having a specific structure, glass fiber, and talc (e.g., Patent Documents 1 and 2), or from a liquid crystal polyester composition containing a fibrous filler and a plate-like filler having a specific number-average aspect ratio (e.g., Patent Document 3), and have excellent moldability, low warpage, and crack resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO 2014 / 50370 [Patent Document 2] JP 2012-214652 A [Patent Document 3] JP 2012-193343 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, CPU sockets have become narrower in pitch due to the increase in the number of pins of CPUs, so the pitch interval of the lattice part in the lattice structure is narrower, and the width of the resin part of the lattice part that constitutes the lattice structure is also narrower. In such narrow-pitch sockets, when the CPU is attached to the socket and the metal terminal part is inserted into the lattice structure, the resin part is more likely to crack, which reduces the yield, and this is an issue. Therefore, a property that does not easily cause cracks even when metal parts are attached, that is, "metal fitting property", is required. In addition, narrow-pitch CPU sockets are manufactured by injection molding of liquid crystal polyester, but in order to fully fill the thin-walled lattice part, they are often manufactured under conditions with high injection molding temperature, injection speed, and injection pressure. Under such conditions, the liquid crystal polyester resin is excessively oriented, and the residual stress of the resulting CPU socket is high, and in plate-shaped molded products such as CPU sockets will have large twists after heat treatment, so "torsion resistance during high-temperature, high-pressure molding", a property that does not easily cause twists even under harsh molding conditions, is also required. Furthermore, as part shapes have become more complex in recent years, the injection pressure is likely to be high where the part shape changes, making flash and jetting more likely to occur. This means that molding stability under high-pressure injection conditions is also required.
[0006] However, the inventions disclosed in Patent Documents 1 to 3 do not disclose a material that can achieve both high levels of metal fitting ability and resistance to twisting during high-temperature, high-pressure molding, which are required for the recent narrow-pitch CPU sockets mentioned above.
[0007] An object of the present invention is to provide a CPU socket that has excellent metal fitting properties even with narrow pitch intervals and has excellent resistance to twisting during high-temperature, high-pressure molding. [Means for solving the problem]
[0008] The present inventors have conducted intensive research to solve the above problems, and have found that a liquid crystal polyester resin composition containing a predetermined amount of inorganic filler with a controlled fiber length distribution in a liquid crystal polyester resin can provide a CPU socket that can solve the above problems, and have arrived at the present invention. That is, the present invention has the following configuration. (1) A CPU socket formed from a liquid crystal polyester resin composition containing 60 to 200 parts by weight of a fibrous filler (B) per 100 parts by weight of a liquid crystal polyester resin (A), wherein the fibrous filler (B) in the liquid crystal polyester resin composition satisfies the following requirement (α): (α): With respect to the fibrous filler (B) in the liquid crystal polyester resin composition, the fibrous fillers (B) having a fiber length of 150 μm or more account for less than 20% of the total fibrous fillers (B) by number, and the fibrous fillers (B) having a fiber length of 20 μm or less account for less than 15% of the total fibrous fillers (B) by number. (2) A CPU socket as described in (1), wherein the fibrous filler (B) having a fiber length of 150 μm or more accounts for less than 6% of the total fibrous filler (B) by number. (3) The CPU socket according to (1) or (2), further comprising 1 to 100 parts by weight of a plate-like filler (C) per 100 parts by weight of the liquid crystal polyester resin (A). (4) The CPU socket according to any one of (1) to (3), wherein the liquid crystal polyester resin (A) is a liquid crystal polyester resin containing the following structural unit (I) and satisfies the following formula (a): 1≦[I]≦20 (a) ([I] indicates the content (mol %) of each of the following structural units (I) relative to 100 mol % of all structural units in the liquid crystal polyester resin.)
[0009] [ka]
[0010] (5) The CPU socket according to any one of (1) to (4), wherein the liquid crystal polyester resin (A) further contains the following structural unit (II) and is a liquid crystal polyester resin that satisfies the following formula (b): 0.1≦[II]≦10 (b)
[0011] [ka]
[0012] (6) The CPU socket according to any one of (1) to (5), wherein the thickness between adjacent lattice structures in the lattice structure is 0.2 mm or less. Effect of the Invention
[0013] The CPU socket of the present invention has excellent metal fitting properties even with narrow pitch intervals and excellent resistance to twisting during high-temperature, high-pressure molding. Such a CPU socket is particularly suitable for use in small electrical and electronic components. [Brief description of the drawings]
[0014] [Figure 1] 1 is a diagram showing a plan view of a CPU socket molded in an embodiment, in which the unit is mm. [Diagram 2] This is a detail of part A in Figure 1. The unit in the figure is mm. [Diagram 3] FIG. 2(a) is a diagram showing a CPU socket viewed in a planar direction from the gate position in FIG. 1, and FIG. 2(b) is a diagram showing a method for evaluating torsion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] <Liquid crystal polyester resin (A)> The liquid crystal polyester resin is a polyester that forms an anisotropic melt phase. Examples of such polyester resins include polyesters that are composed of structural units selected from oxycarbonyl units, dioxy units, dicarbonyl units, etc., which will be described later, so as to form an anisotropic melt phase. The liquid crystal polyester resin (A) preferably contains 20-80 mol% of structural units derived from aromatic hydroxycarboxylic acid, 10-40 mol% of structural units derived from aromatic diol, and 10-40 mol% of structural units derived from aromatic dicarboxylic acid, based on 100 mol% of all structural units of the liquid crystal polyester resin (A).
[0017] Next, the structural units constituting the liquid crystal polyester resin will be described.
[0018] From the viewpoint of obtaining a CPU socket having excellent metal fitting property and excellent resistance to torsion during high-temperature, high-pressure molding, the liquid crystal polyester resin (A) used in the present invention preferably contains, as an oxycarbonyl unit, the following structural unit (III) derived from p-hydroxybenzoic acid in an amount of 25 to 75 mol % relative to 100 mol % of all structural units in the liquid crystal polyester resin (A). It is preferably 30 mol % or more, more preferably 40 mol % or more, and even more preferably 45 mol % or more. On the other hand, it is preferably 65 mol % or less, more preferably 50 mol % or less, and even more preferably 55 mol % or less.
[0019] [ka]
[0020] From the viewpoint of obtaining a CPU socket having excellent metal fitting properties, the liquid crystal polyester resin (A) used in the present invention preferably contains the following structural unit (IV) derived from 6-hydroxy-2-naphthoic acid as an oxycarbonyl unit in an amount of 1 to 20 mol % relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). The structural unit (IV) has a naphthalene ring structure and has a different molecular chain length from the structural unit (I) having a benzene ring, so that the molecular chain of the liquid crystal polyester resin can be suppressed from being tightly packed while maintaining liquid crystallinity. This makes the resin flexible and improves the metal fitting properties. It is preferably 2 mol % or more, more preferably 3 mol % or more. On the other hand, it is preferably 15 mol % or less, more preferably 10 mol % or less.
[0021] [ka]
[0022] From the viewpoint of obtaining a CPU socket having excellent resistance to twisting during high-temperature, high-pressure molding, the liquid crystal polyester resin (A) of the present invention preferably contains, as a dioxy unit, 2 to 20 mol % of the following structural unit (I) derived from hydroquinone, relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). By using the structural unit (I) as a dioxy unit, the linearity of the liquid crystal polyester resin is improved, and the resistance to twisting during high-temperature, high-pressure molding is improved. It is preferably contained at 5 mol % or more, more preferably at 8 mol % or more. It is more preferably 18 mol % or less, and even more preferably 16 mol % or less.
[0023] [ka]
[0024] From the viewpoint of obtaining a CPU socket having excellent metal fitting properties, the liquid crystal polyester resin (A) of the present invention preferably contains 1 to 25 mol % of structural units (V) derived from 4,4'-dihydroxybiphenyl as dioxy units relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). By containing dioxy units having a molecular chain length longer than other monomers, the packing of the molded article surface is appropriately disordered, and the metal fitting properties are improved. 3 mol % or more is more preferable, and 5 mol % or more is even more preferable. On the other hand, 20 mol % or less is more preferable, and 15 mol % or less is even more preferable.
[0025] [ka]
[0026] From the viewpoint of obtaining a CPU socket having excellent resistance to torsion during high-temperature, high-pressure molding, the liquid crystal polyester resin (A) of the present invention preferably contains, as dicarbonyl units, 2 to 35 mol % of structural units (VI) derived from terephthalic acid relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). It is preferably 5 mol % or more, more preferably 10 mol % or more, and even more preferably 15 mol % or more. On the other hand, it is preferably 30 mol % or less, more preferably 25 mol % or less.
[0027] [ka]
[0028] From the viewpoint of obtaining a CPU socket having excellent metal fitting properties, the liquid crystal polyester resin (A) of the present invention preferably contains 0.1 to 10 mol % of the structural unit (II) derived from isophthalic acid as a dicarbonyl unit relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). Since the structural unit (II) has a significantly curved structure compared to other monomers, the packing of the liquid crystal polyester resin can be appropriately disturbed, and a CPU socket having improved metal fitting properties can be obtained. More preferably, 0.2 mol % or more, more preferably 8 mol % or less, more preferably 6 mol % or less, and even more preferably 4 mol % or less.
[0029] [ka]
[0030] In addition to the above structural units, structural units derived from ethylene glycol, p-aminobenzoic acid, p-aminophenol, etc. may be contained within the range that does not impair the liquid crystallinity or other characteristics.
[0031] The monomers serving as raw materials for forming each of the structural units described above are not particularly limited as long as they have a structure capable of forming each of the structural units. In addition, acylation products of the hydroxyl groups of such monomers, esterification products of the carboxyl groups, acid halides, acid anhydrides and other carboxylic acid derivatives may be used.
[0032] The method for calculating the content of each structural unit in the liquid crystal polyester resin is as follows. First, the liquid crystal polyester resin is pulverized, and then tetramethylammonium hydroxide is added. The content can be determined by pyrolysis GC / MS measurement using a Shimadzu GCMS-QP5050A. The content of structural units that are not detected or are below the detection limit is calculated as 0 mol%.
[0033] The melting point (Tm) of the liquid crystal polyester resin (A) is preferably 280°C or higher, more preferably 300°C or higher, and even more preferably 320°C or higher, from the viewpoint of obtaining a CPU socket having excellent heat resistance and therefore excellent resistance to twisting during high-temperature, high-pressure molding. On the other hand, the melting point (Tm) of the liquid crystal polyester resin (A) is preferably 370°C or lower, more preferably 360°C or lower, and even more preferably 350°C or lower, from the viewpoint of obtaining a CPU socket having excellent processability. The melting point (Tm) is measured by differential scanning calorimetry. Specifically, first, the liquid crystal polyester resin (A) is heated from room temperature at a temperature increase rate of 20°C / min to obtain an endothermic peak temperature (Tm 1 ) is observed. 1 ) and then the endothermic peak temperature (Tm 1 The polymer is then held at a temperature of +20°C for 5 minutes. The polymer is then cooled to room temperature at a temperature drop of 20°C / min. The polymer is then heated at a temperature rise of 20°C / min to obtain the endothermic peak temperature (Tm 2 The melting point (Tm) is the endothermic peak temperature (Tm 2 )
[0034] The melt viscosity of the liquid crystal polyester resin is preferably 3 Pa·s or more, more preferably 4 Pa·s or more, and even more preferably 5 Pa·s or more, from the viewpoint of obtaining a CPU socket having excellent resistance to torsion during high-temperature, high-pressure molding due to excellent strength. In addition, by having excellent fluidity, residual stress is reduced to obtain a CPU socket having excellent resistance to torsion during high-temperature, high-pressure molding. In addition, by making the liquid crystal polyester resin relatively low in viscosity, when preparing the liquid crystal polyester resin composition used in the present invention by melt kneading using an extruder, excessive pulverization due to contact between the fibrous filler (B) and the liquid crystal polyester resin (A) during melt kneading is suppressed, so that the fibrous filler (B) having a fiber length of 20 μm or less in the liquid crystal polyester resin composition can be easily controlled to less than 15%, and therefore the melt viscosity of the liquid crystal polyester resin is preferably 30 Pa·s or less, more preferably 20 Pa·s or less, and even more preferably 10 Pa·s or less.
[0035] The melt viscosity is a value measured by a Koka type flow tester at a temperature of the melting point (Tm) of the liquid crystal polyester resin + 20° C. under the condition of a shear rate of 1000 / sec.
[0036] <Method for producing liquid crystal polyester resin (A)> The method for producing the liquid crystal polyester resin (A) used in the present invention is not particularly limited, and can be produced in accordance with a known polyester polycondensation method. Examples of known polyester polycondensation methods include the following, for example, liquid crystal polyester resin (A) consisting of a structural unit derived from p-hydroxybenzoic acid, a structural unit derived from 6-hydroxy-2-naphthoic acid, a structural unit derived from 4,4'-dihydroxybiphenyl, a structural unit derived from hydroquinone, and a structural unit derived from terephthalic acid and isophthalic acid.
[0037] (1) A method for producing a liquid crystal polyester resin (A) from p-acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid, 4,4'-diacetoxybiphenyl, diacetoxybenzene, terephthalic acid, and isophthalic acid by a deacetic acid condensation polymerization reaction.
[0038] (2) A method for producing a liquid crystal polyester resin (A) by reacting p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 4,4'-dihydroxybiphenyl, hydroquinone, terephthalic acid, and isophthalic acid with acetic anhydride to acetylate the phenolic hydroxyl groups, followed by deacetylation polymerization.
[0039] (3) A method for producing a liquid crystal polyester resin (A) by a dephenolation polycondensation reaction of phenyl p-hydroxybenzoate, phenyl 6-hydroxy-2-naphthoate, 4,4'-dihydroxybiphenyl, hydroquinone, diphenyl terephthalate, and diphenyl isophthalate.
[0040] (4) A method in which a predetermined amount of diphenyl carbonate is reacted with aromatic carboxylic acids, such as p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, terephthalic acid, and isophthalic acid, to form the phenyl esters, respectively, and then an aromatic dihydroxy compound, such as 4,4'-dihydroxybiphenyl or hydroquinone, is added to carry out a dephenolation polycondensation reaction to produce a liquid crystal polyester resin (A).
[0041] Among these, the method (2) of reacting p-hydroxybenzoic acid, 4,4'-dihydroxybiphenyl, hydroquinone, terephthalic acid, and isophthalic acid with acetic anhydride to acetylate the phenolic hydroxyl groups, followed by a deacetylase polycondensation reaction to produce the liquid crystal polyester resin (A) is preferably used because it is industrially excellent in controlling the terminal structure and the degree of polymerization of the liquid crystal polyester resin (A).
[0042] As a method for producing the liquid crystal polyester resin (A) used in the present invention, it is also possible to complete the polycondensation reaction by a solid-phase polymerization method. Examples of the treatment by the solid-phase polymerization method include the following method. First, the polymer or oligomer of the liquid crystal polyester resin (A) is pulverized by a pulverizer. The pulverized polymer or oligomer is heated under a nitrogen stream or reduced pressure to polycondense to a desired degree of polymerization, thereby completing the reaction. The heating can be performed for 1 to 50 hours at a temperature in the range of the melting point of the liquid crystal polyester resin (A) -50°C to the melting point -5°C (for example, 200 to 300°C).
[0043] <Fiber filler (B)> The liquid crystal polyester resin composition used in the present invention is characterized by containing 60 to 200 parts by weight of fibrous filler (B) relative to 100 parts by weight of liquid crystal polyester resin (A). By increasing the content of fibrous filler (B) relatively, the liquid crystal polyester resin is not excessively oriented during molding, so that a CPU socket having improved metal fitting property and torsion resistance during high-temperature, high-pressure molding can be obtained. In addition, by increasing the content of fibrous filler (B) relatively, when the liquid crystal polyester resin composition used in the present invention is prepared by melt kneading using an extruder, the fibrous filler comes into contact with each other and breaks moderately during melt kneading, so that it becomes easy to control the fibrous filler (B) having a fiber length of 150 μm or more in the liquid crystal polyester resin composition to less than 20%. It is preferably 70 parts by weight or more, more preferably 80 parts by weight or more. On the other hand, it is preferably 180 parts by weight or less, more preferably 160 parts by weight or less. If the content of inorganic filler (B) is less than 60 parts by weight, it becomes difficult to control the fiber length of the fibrous filler (B), making it impossible to achieve both metal fitting properties and twist resistance during high-temperature, high-pressure molding. If the content is more than 200 parts by weight, the fibrous filler will protrude from the CPU socket surface, reducing metal fitting properties.
[0044] The inorganic filler (B) used in the present invention is not particularly limited, and examples thereof include glass fibers, stainless steel fibers, metal fibers such as aluminum fibers and brass fibers, gypsum fibers, ceramic fibers, asbestos fibers, zirconia fibers, alumina fibers, silica fibers, titanium oxide fibers, silicon carbide fibers, rock wool, potassium titanate whiskers, barium titanate whiskers, aluminum borate whiskers, silicon nitride whiskers, and needle-shaped titanium oxide. It is more preferable to use glass fibers from the viewpoint of excellent mechanical strength such as tensile strength and bending strength, heat resistance, dimensional stability and availability, and easy control of the fiber length described later. The type of glass fiber is not particularly limited as long as it is generally used for reinforcing resins, and examples include chopped strands of long fiber type and short fiber type, milled fiber, etc., but it is preferable to use glass fibers with a number average fiber length of 30 to 150 μm from the viewpoint of easy control of the fiber length of the fibrous filler described later to an appropriate value. More preferably, the number average fiber length is 40 to 100 μm. The method for calculating the number average fiber length of the fibrous filler (B) used as a raw material before blending is described below. The fibrous filler (B) used as a raw material is dispersed on a slide glass using liquid paraffin, and multiple images are observed using a stereomicroscope (Leica "M205C") at a dispersion state and magnification (approximately 100x) such that approximately 100 to 200 fibrous fillers (B) are observed in the observation image. Using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015"), 1000 fibrous fillers are randomly selected and the fiber length is measured. The total value of the fiber length obtained is divided by the number of measured fibers (1000) to calculate the number average fiber length.
[0045] The fibrous filler (B) in the liquid crystal polyester resin composition of the present invention is characterized in that it satisfies the following requirement (α) (hereinafter, the fiber length of the fibrous filler in the liquid crystal polyester resin composition described in requirement (α) may be simply referred to as the "fiber length of the fibrous filler (B)"). (α): With respect to the fibrous filler (B) in the liquid crystal polyester resin composition, the fibrous fillers (B) having a fiber length of 150 μm or more account for less than 20% of the total fibrous fillers (B) by number, and the fibrous fillers (B) having a fiber length of 20 μm or less account for less than 15% of the total fibrous fillers (B) by number.
[0046] When the fibrous filler (B) having a fiber length of 150 μm or more is 20% or more, the tip of the fibrous filler is likely to protrude from the surface of the molded product, especially in the case of a molded product with a complex shape having a large number of thin lattices such as a CPU socket with a narrow pitch interval. In such a CPU socket, when a CPU socket having a metal terminal is attached, the metal part is caught by the floating fibrous filler, and cracks occur in the socket part. That is, the metal fitting property is reduced. In addition, the filling property into the mold is also reduced, so that residual stress in the molded product is likely to remain, and the torsion resistance during high-temperature and high-pressure molding is also reduced. On the other hand, when the fibrous filler (B) having a fiber length of 20 μm or less is 15% or more, the reinforcing effect in the CPU socket lattice part is insufficient, and the metal fitting property is reduced. In addition, the reinforcing effect of the CPU socket structure itself is also insufficient, and the torsion resistance especially after heat treatment is reduced. From the above, by making the fiber length of the fibrous filler (B) in the liquid crystal polyester resin composition satisfy the above requirement (α), it is possible to achieve both metal fitting property and torsion resistance during high-temperature and high-pressure molding. The fibrous filler (B) having a fiber length of 150 μm or more is preferably 15% or less, more preferably 10% or less, based on the number of fibers. In addition, from the viewpoint of obtaining a CPU socket having particularly excellent torsion resistance during high-temperature and high-pressure molding and excellent molding stability, it is particularly preferable that it is 6% or less. Moreover, the fibrous filler (B) having a fiber length of 20 μm or less is preferably 13% or less, more preferably 10% or less, and even more preferably 7% or less.
[0047] As a method for controlling the fiber length of the fibrous filler (B) in the liquid crystal polyester resin composition of the present invention to a suitable range, (1) the content of the fibrous filler (B) in the liquid crystal polyester resin composition is set to the above-mentioned preferred range, (2) the melt viscosity of the liquid crystal polyester (A) is set to the above-mentioned preferred range, (3) the liquid crystal polyester resin composition is produced by the preferred method described later in <Production method of liquid crystal polyester resin composition>, and (4) milled fibers having a number average fiber length in the above-mentioned preferred range are used as raw materials. In addition, (5) the fiber length of the fibrous filler (B) can also be controlled to a suitable range by using a fibrous filler with a controlled fiber length distribution by removing fibrous fillers with long or short fiber lengths using a sieve.
[0048] The method for calculating the fiber length of the fibrous filler (B) is described below. The liquid crystal polyester resin composition is heated in air at 550 ° C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material is obtained as the fibrous filler (B). The obtained fibrous filler (B) is dispersed on a slide glass using liquid paraffin, and a stereomicroscope (Leica "M205C") is used to observe multiple sheets at a dispersion state and magnification (about 100 times) in which about 100 to 200 fibrous fillers (B) are observed in the observation image, and 1000 fibrous fillers are randomly selected and their fiber lengths are measured using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to determine the number of fibrous fillers (B) with a fiber length of 150 μm or more and the number of fibrous fillers (B) with a fiber length of 20 μm or less, and their respective presence ratios (%) are calculated.
[0049] The liquid crystal polyester resin composition used in the present invention may further contain conventional additives selected from antioxidants, heat stabilizers (e.g., hindered phenols, phosphites, thioethers, and their substitutes), ultraviolet absorbers (e.g., resorcinol, salicylate), color inhibitors such as phosphites and hypophosphites, lubricants and mold release agents (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, and polyethylene wax), colorants including dyes or pigments, conductive agents or colorants such as carbon black, crystal nucleating agents, plasticizers, flame retardants (bromine-based flame retardants, phosphorus-based flame retardants, red phosphorus, silicone-based flame retardants, etc.), flame retardant assistants, and antistatic agents, within the scope of the present invention.
[0050] <Plate-shaped filler (C)> The liquid crystal polyester resin composition used in the present invention preferably contains 1 to 100 parts by weight of a plate-like filler (C) relative to 100 parts by weight of the liquid crystal polyester resin (A). Unlike fibrous fillers, plate-like fillers have a wide distribution of particle size and aspect ratio, so that the orientation of the LCP during melt flow can be moderately disturbed. In an excessively oriented state, when high pressure conditions are applied during molding, the LCP fills first, which makes it easier for flash and jetting to occur, thereby reducing molding stability. Therefore, the incorporation of the plate-like filler (C) improves molding stability under high pressure conditions. The amount of the plate-like filler to be incorporated is preferably 1 to 50 parts by weight, more preferably 5 to 30 parts by weight, relative to 100 parts by weight of the liquid crystal polyester resin (A), from the viewpoint of easily controlling the fiber length of the above-mentioned fibrous filler (B) within an appropriate range and achieving a balance between metal fitting property, torsion resistance during high-temperature and high-pressure molding, and molding stability under high pressure conditions.
[0051] The plate-like filler referred to here means a filler having a ratio of average particle size to average thickness of 2 or more. The average particle size and average thickness can be determined by the following method. First, 3 g of the liquid crystal polyester resin composition is heated in air at 550°C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material is obtained. The average particle size is determined by weighing 100 mg of the resulting residue, dispersing it on a slide glass using liquid paraffin, and observing multiple images using a stereomicroscope (Leica "M205C") at a dispersion state and magnification (approximately 500 to 1000 times) where about 50 to 100 plate-like fillers are observed in the observation image, and randomly selecting 1000 plate-like fillers using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to measure the major axis of the plate-like fillers, and calculating the number average value. The average thickness was determined by observing the residue with a scanning electron microscope (SEM) ("JSM-6360LV" manufactured by JEOL Ltd.) at a magnification of 2000 times, measuring the thicknesses of 10 randomly selected plate-like fillers from the image, and calculating the number average value by adjusting the observation direction and angle.
[0052] Examples of the plate-like filler include mica, talc, kaolin, glass flakes, clay, molybdenum disulfide, and wollastonite. From the viewpoint of improving molding stability under high pressure conditions, talc or mica is preferred.
[0053] Powdered or granular inorganic fillers may be used in combination as long as the effects of the present invention are not impaired. Examples of powdered or granular fillers include silica, glass beads, titanium oxide, zinc oxide, and calcium polyphosphate.
[0054] The filler used in the present invention may have its surface treated with a known coupling agent (e.g., a silane coupling agent, a titanate coupling agent, etc.) or other surface treatment agent. In addition, the filler used in the present invention may be used in combination of two or more kinds.
[0055] <Method of producing liquid crystal polyester resin composition> As a method for blending the fibrous filler (B) and other additives with the liquid crystal polyester resin (A) to obtain a liquid crystal polyester resin composition, for example, a dry blend method for blending the fibrous filler (B) and other solid additives with the liquid crystal polyester resin (A), a solution blending method for blending the fibrous filler (B) and other liquid additives with the liquid crystal polyester resin (A), a method for adding the fibrous filler (B) and other additives during polymerization of the liquid crystal polyester resin (A), and a method for melt-kneading the fibrous filler (B) and other additives with the liquid crystal polyester resin (A) can be used. Among them, the melt-kneading method is preferred from the viewpoint of controlling the fiber length of the fibrous filler (B) to an appropriate value.
[0056] For the melt kneading, a known method can be used. For example, a Banbury mixer, a rubber roll machine, a kneader, a single-screw or twin-screw extruder, etc. can be mentioned. Among them, a twin-screw extruder is preferred from the viewpoint of controlling the fiber length of the fibrous filler (B) to an appropriate value.
[0057] From the viewpoint of controlling the fiber length of the fibrous filler to an appropriate value, the set temperature of the cylinder of the extruder during melt kneading is preferably set within a range of +10 to +40°C of the melting point of the liquid crystal polyester resin (A). By setting the cylinder temperature relatively high, excessive pulverization due to contact between the fibrous filler (B) and the liquid crystal polyester resin (A) during melt kneading is suppressed, so that the fibrous filler (B) having a fiber length of 20 μm or less in the liquid crystal polyester resin composition can be easily controlled to less than 15%. +15°C or higher is more preferable, and +20°C or higher is even more preferable.
[0058] The rotational circumferential speed (m / min) of the screw during melt kneading is preferably 10 to 30 m / min. By setting it in this range, the fiber length of the fibrous filler (B) can be controlled to an appropriate value. It is more preferable to set it in the range of 10 to 20 m / min, and even more preferable to set it in the range of 10 to 16 m / min. The rotational circumferential speed (m / min) of the screw can be calculated by screw diameter (m) x pi x rotation speed (rpm).
[0059] In the present invention, when a twin-screw extruder is used, a combination of full flight and kneading discs is used as the screw configuration. From the viewpoint of controlling the fiber length of the fibrous filler (B) to an appropriate value, the ratio of the total length of the kneading discs (hereinafter sometimes referred to as the "kneading zone") to the total length of the screws is preferably in the range of 5 to 50%, more preferably in the range of 10 to 40%, and most preferably in the range of 12 to 30%.
[0060] The melt-kneading method includes 1) a method in which the liquid crystal polyester resin (A), the fibrous filler (B) and other additives are fed from a feeder at once and kneaded together (lump-kneading method), 2) a method in which the liquid crystal polyester resin (A) and other additives are fed from a feeder and kneaded together, and then the fibrous filler (B) is added from a side feeder and kneaded together (side feed method), and 3) a method in which a liquid crystal polyester composition (master pellet) containing a high concentration of the liquid crystal polyester resin (A), the fibrous filler (B) and other additives is prepared, and then the master pellet is kneaded with the liquid crystal polyester resin (A) to a specified concentration (master pellet method). The side feed method described in 2) is preferred from the viewpoint that excessive pulverization of the fibrous filler (B) can be suppressed and the fibrous filler (B) having a fiber length of 20 μm or less in the liquid crystal polyester resin composition can be easily controlled to less than 15%.
[0061] <CPUソケット> The CPU socket of the present invention is formed from a liquid crystal polyester resin composition containing 60 to 200 parts by weight of a fibrous filler (B) per 100 parts by weight of a liquid crystal polyester resin (A), and the fibrous filler (B) in the liquid crystal polyester resin composition satisfies the following requirement (α). (α): With respect to the fibrous filler (B) in the liquid crystal polyester resin composition, fibrous fillers (B) having a fiber length of 150 μm or more account for less than 20% of the total fibrous fillers (B), and fibrous fillers (B) having a fiber length of 20 μm or less account for less than 15% of the total fibrous fillers (B).
[0062] The present inventors have found that a liquid crystal polyester resin composition containing a relatively large amount of fibrous filler (B) in which the ratio of a specific fiber length is controlled as described in the above requirement (α) has excellent metal fitting properties and torsion resistance during high-temperature, high-pressure molding, which can be evaluated by the method described below, due to the compatibility of reinforcing effect and reduction of residual stress. Furthermore, they have found that a liquid crystal polyester resin composition having such effects is suitable for CPU sockets having a precise lattice structure, which have become thinner and have narrower pitches in recent years.
[0063] The metal fitting property can be evaluated by the following method. The pellets of the liquid crystal polyester resin composition are dried with hot air at 150°C for 3 hours using a hot air dryer, and then subjected to an injection molding machine (α30C manufactured by Fanuc) to obtain a metal insertion test piece having a thickness of 3 mm and 20 holes of 1.5 mm x 1.5 mm at a pitch of 2.8 mm under molding conditions of a cylinder temperature of the melting point of the liquid crystal polyester resin + 40°C, a mold temperature of 90°C, and an injection speed of 300 mm / s. A 1.6 mm x 1.6 mm brass square rod is inserted into each of the square holes of the obtained test piece, and the number of cracks generated among the square holes is checked. The fewer the number of cracks, the better the metal fitting property, and 0 to 6 is preferable.
[0064] The twist resistance during high-temperature, high-pressure molding can be evaluated by the following method. After drying the pellets of the liquid crystal polyester resin composition with hot air at 150°C for 3 hours using a hot air dryer, the pellets are subjected to an injection molding machine (α30C manufactured by Fanuc) and injection-molded into the CPU sockets shown in Figs. 1 and 2 by 10 shots under relatively high-temperature, high-pressure molding conditions, with the cylinder temperature set to the melting point of the liquid crystal polyester resin +40°C, the mold temperature set to 90°C, and the injection speed set to 300mm / s. The average twist amount is measured for the 10 CPU sockets obtained. Here, the twist amount is explained with reference to Fig. 3. Fig. 3(a) shows a schematic diagram of the CPU socket shown in Fig. 1 as viewed in a planar direction from the gate (10) side, and S1 and S2 are set on both side surfaces as shown in Figs. 3(a) and (b). At this time, the plane connecting S1 and S2 with a straight line is taken as the reference plane L1. Next, as shown in FIG. 3(b), when the CPU socket is twisted, a maximum displacement plane L2 that is parallel to L1 from the maximum displacement point is set, and the average distance between L1 and L2 is measured. The smaller the value, the better the torsion resistance, and it is preferably 0 to 17 μm. Next, the 10 CPU sockets are left to stand in a hot air oven heated to 270° C. for 3 minutes, and the amount of twist after the heat treatment is measured in the same manner as described above. The smaller the value, the better the torsion resistance, and it is preferably 0 to 29 μm.
[0065] The shape of the CPU socket is not particularly limited as long as it has a lattice structure inside the outer frame, and may have an opening of an appropriate size within the lattice structure.
[0066] The CPU socket in the embodiment will be described in detail. For example, the CPU socket shown in FIG. 1 and FIG. 2 is a plate-shaped molded product of length 39.85 mm × width 41.70 mm × height (thickness) 1.0 mm, molded by injection molding from three gate positions 1, and has a lattice structure 3 inside from positions 2.0 mm thick from the upper and lower ends of the outer frame portion 2. Also, a resin portion of 2 mm thick is provided in the center of the width 41.70 mm. The lattice structure 3 includes a lattice portion consisting of a resin portion and a pin insertion hole 4, and a lattice portion with a pitch interval of 1.2 mm and a resin portion of 0.15 mm is formed inside the outer frame portion 2, and further, an opening is provided in the center of the lattice structure 3 in an inner frame portion of 1.2 mm thick. A lattice portion of 15 columns × 2 × 30 rows is formed, but the number of lattice portions is 780 because of the opening.
[0067] The lattice structure referred to here is a structure in which a number of through holes (pin insertion holes) are formed at a predetermined interval in the vertical and horizontal directions by a number of resin parts extending vertically and horizontally on the plate surface of the CPU socket. The shape of the through holes is rectangular in Figures 1 and 2, but is not particularly limited and may be round, etc.
[0068] The lattice portion here refers to a portion including one through hole and a resin portion between the through hole and the adjacent through hole. The number of the lattice portions can be selected as necessary, and can be, for example, 500 to 10,000.
[0069] The pitch here is the sum of the width of the resin part of the lattice part constituting the lattice structure and the width of the through hole. The width of the through hole is the longest straight line distance between adjacent resin parts. The pitch can be selected as needed, but from the viewpoint of manufacturing a high-performance CPU socket with many pins and space saving, it is preferably 1.5 mm or less, more preferably 1.3 mm or less, and even more preferably 1.2 mm or less. On the other hand, from the viewpoint of excellent metal fitting property and torsion resistance during high-temperature and high-pressure molding, it is preferably 0.6 mm or more, more preferably 0.7 mm or more. It is even more preferable that it is 0.8 mm or more. In addition, the width of the resin part of the lattice part constituting the lattice structure can be selected as needed, but from the viewpoint of manufacturing a high-performance CPU socket with many pins and space saving, it is preferably 0.20 mm, more preferably 0.18 mm or less, and even more preferably 0.16 mm or less. On the other hand, from the viewpoint of excellent metal fitting property and torsion resistance during high-temperature and high-pressure molding, it is preferably 0.08 mm or more, more preferably 0.10 mm or more, and even more preferably 0.12 mm or more. The liquid crystal polyester resin composition used in the present invention makes it possible to obtain a CPU socket that has excellent metal fitting properties and excellent resistance to twisting during high-temperature, high-pressure molding, even if it has such a very thin portion.
[0070] The liquid crystal polyester resin composition used in the present invention can be molded into a CPU socket by ordinary molding methods such as injection molding, extrusion molding, and press molding, and can be processed into a CPU socket having excellent surface appearance (color tone), mechanical properties, and heat resistance. In particular, injection molding is preferable from the viewpoint of processability. When injection molding, it is preferable to mold at a melting point +50°C or less from the viewpoint of suppressing deterioration of the liquid crystal polyester resin composition and obtaining a CPU socket having excellent metal fitting properties and torsion resistance.
[0071] The mold temperature is preferably 70° C. or higher from the viewpoint of filling the liquid crystal polyester resin composition, and is preferably 130° C. or lower from the viewpoint of suppressing defects such as burrs. EXAMPLES
[0072] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The liquid crystal polyester resin (A) described in the production examples was evaluated in the following items (1) to (3), and the results are shown in Table 1.
[0073] [Table 1]
[0074] (1) Composition analysis of liquid crystal polyester resin (A) To 0.1 mg of the ground liquid crystal polyester resin, 2 μL of a 25% methanol solution of tetramethylammonium hydroxide was added, and pyrolysis GC / MS measurement was performed using a Shimadzu GCMS-QP5050A to determine the composition ratio of each component in the liquid crystal polyester resin.
[0075] (2) Melting point (Tm) measurement of liquid crystal polyester resin (A) The endothermic peak temperature (Tm 1 ), Tm 1 After keeping the temperature at +20°C for 5 minutes, the sample was cooled to room temperature at a temperature drop rate of 20°C / min, and then heated again at a temperature rise rate of 20°C / min. The endothermic peak temperature observed when the sample was heated was taken as the melting point (Tm).
[0076] (3) Melt Viscosity of Liquid Crystal Polyester Resin (A) The melt viscosity of the liquid crystal polyester resin was measured at Tm+20° C. and a shear rate of 1000 / s using a high-performance flow tester CFT-500D (orifice 0.5φ×10 mm) (manufactured by Shimadzu Corporation).
[0077] [Production Example 1] In a 5L reaction vessel equipped with an agitator and a distillation tube, 808 parts by weight of p-hydroxybenzoic acid (HBA), 88 parts by weight of 6-hydroxy-2-naphthoic acid (HNA), 229 parts by weight of 4,4'-dihydroxybiphenyl (DHB), 161 parts by weight of hydroquinone (HQ), 428 parts by weight of terephthalic acid (TPA), 19 parts by weight of isophthalic acid (IPA) and 1278 parts by weight of acetic anhydride (1.07 equivalents of phenolic hydroxyl groups in total) were charged, and the mixture was reacted at 145°C for 120 minutes while stirring under a nitrogen gas atmosphere, and then the temperature was raised from 145°C to 360°C over 4 hours. Thereafter, the polymerization temperature was maintained at 360°C, the pressure was reduced to 1.0mmHg (133Pa) over 1.0 hour, and the reaction was continued until the polymerization was completed when a predetermined stirring torque was reached. Next, the polymer was discharged in the form of strands through a die having one circular discharge port with a diameter of 6 mm, and pelletized with a cutter to obtain a liquid crystal polyester resin (A-1).
[0078] [Production Example 2] In a 5L reaction vessel equipped with an agitator and a distillation tube, 873 parts by weight of HBA, 370 parts by weight of DHB, 77 parts by weight of HQ, 292 parts by weight of TPA, 156 parts by weight of IPA, and 1278 parts by weight of acetic anhydride (1.07 equivalents of phenolic hydroxyl groups in total) were charged, and the mixture was reacted at 145°C for 120 minutes while stirring under a nitrogen gas atmosphere, and then the temperature was raised from 145°C to 335°C over 4 hours. Thereafter, the polymerization temperature was maintained at 335°C, the pressure was reduced to 1.0mmHg (133Pa) over 1.0 hour, and the reaction was continued until the polymerization was completed when a predetermined stirring torque was reached. Next, the polymer was discharged in the form of strands through a die having one circular discharge port with a diameter of 6 mm, and pelletized with a cutter to obtain a liquid crystal polyester resin (A-2).
[0079] [Production Example 3] A liquid crystal polyester resin (A-3) was obtained in the same manner as in Example 1, except that the monomer charges were changed to 743 parts by weight of HBA, 176 parts by weight of HNA, 153 parts by weight of DHB, 206 parts by weight of HQ, and 447 parts by weight of TPA.
[0080] [Production Example 4] A liquid crystal polyester resin (A-4) was obtained in the same manner as in Example 1, except that the monomer charges were changed to 808 parts by weight of HBA, 88 parts by weight of HNA, 501 parts by weight of DHB, 408 parts by weight of TPA, and 39 parts by weight of IPA.
[0081] [Production Example 5] A liquid crystal polyester resin (A-5) was obtained in the same manner as in Production Example 2, except that the ultimate stirring torque after reduced pressure was set higher.
[0082] Inorganic filler (B) (B-1) Glass fiber: Glass fiber manufactured by Nippon Electric Glass Co., Ltd. having a number average fiber length of 60 μm and a fiber diameter of 9 μm was used. (B-2) Glass fiber: EPG140M-10A (manufactured by Nippon Electric Glass Co., Ltd., number average fiber length 140 μm, fiber diameter 9 μm) (B-3) Glass fiber: ECS03T-747H (manufactured by Nippon Electric Glass Co., Ltd., fiber length (cut length) 3 mm, fiber diameter 10.5 μm) (B-4) Glass fiber: The glass fiber of (B-1) was sieved using a 120 mesh sieve to have a number average fiber length as described below, and the glass fiber that passed through the sieve was used. (Average fiber length before blending: 42 μm)
[0083] Plate-shaped filler (C) (C-1) Talc: RL217 (manufactured by Fuji Talc Industries Co., Ltd.) (C-2) Mica: AB-25S (manufactured by Yamaguchi Mica Co., Ltd.)
[0084] [Examples 1 to 9, Comparative Examples 1 and 4] The liquid crystal polyester resin (A), fibrous filler (B) and plate-like filler (C) obtained in each production example were introduced into a twin-screw extruder (TEX-30α, manufactured by Japan Steel Works) with a screw diameter of 30 mm and L / D 35 and equipped with a co-rotating vent, in the amounts shown in Table 2. The liquid crystal polyester resin (A) was added from the end of the twin-screw extruder, and the fibrous filler (B) and plate-like filler (C) were added by installing a side feeder between the end of the twin-screw extruder and the vent (side feed method). The cylinder temperature was set to the melting point of the liquid crystal polyester resin (A) + 25°C, and the kneading zone was incorporated in the middle of the screw from the side feeder to the discharge port, with the ratio being 15% of the total screw length. The melt kneading was performed under the conditions of a screw rotational peripheral speed of 14 m / min, discharged in the form of a strand, solidified through a cooling bath, and then pelletized by a strand cutter, which was used for the evaluations of (4) to (6).
[0085] [Comparative Examples 2 and 3] The liquid crystal polyester resin (A) and fibrous filler (B) obtained in each production example were introduced into a twin-screw extruder (TEX-30α, manufactured by Japan Steel Works) with a screw diameter of 30 mm and L / D 35 and equipped with a co-rotating vent, in the amounts shown in Table 2. The liquid crystal polyester resin (A) and the fibrous filler (B) were added by installing a side feeder between the initial charge section and the vent section (side feed method). The cylinder temperature was set to the melting point of the liquid crystal polyester resin (A) + 10°C, and melt kneading was performed under the condition of a screw rotation peripheral speed of 19 m / min, discharged in the form of a strand, solidified through a cooling bath, and then pelletized by a strand cutter, which was used for the evaluations of (4) to (6).
[0086] (4) Fiber length of the fibrous filler (B) in the liquid crystal polyester resin composition 5 g of pellets of the liquid crystal polyester resin composition obtained in each Example and Comparative Example were heated in air at 550 ° C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material was obtained as a fibrous filler (B). The obtained fibrous filler (B) was dispersed on a slide glass using liquid paraffin, and a stereomicroscope (Leica "M205C") was used to observe multiple sheets at a dispersion state and magnification (about 100 times) in which about 100 to 200 fibrous fillers (B) were observed in the observation image, and 1000 fibrous fillers were randomly selected and the fiber length was measured using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to determine the number of fibrous fillers (B) with a fiber length of 150 μm or more and the number of fibrous fillers (B) with a fiber length of 20 μm or less, and their presence ratios (%) were calculated. In Table 2, the respective percentages obtained are shown as "proportion of 150 μm or more" and "proportion of 20 μm or less."
[0087] (5) Metal fitting The pellets of the liquid crystal polyester resin composition obtained in each Example and Comparative Example were dried with hot air at 150 ° C. for 3 hours using a hot air dryer, and then subjected to a FANUC α30C injection molding machine (manufactured by FANUC). The cylinder temperature was set to the melting point of the liquid crystal polyester resin + 40 ° C., the mold temperature was set to 90 ° C., and the injection speed was set to 300 mm / s. Under the molding conditions, a metal insertion test piece having a thickness of 3.0 mm and 20 holes of 1.5 mm x 1.5 mm at a pitch of 2.8 mm was obtained. A 1.6 mm x 1.6 mm brass square rod was inserted into each of the square holes of the obtained test piece, and the number of cracks that occurred among the square holes was checked. The fewer the number, the better the metal fitting property.
[0088] (6) Twist resistance during high-temperature, high-pressure molding The pellets of the liquid crystal polyester resin composition obtained in each Example and Comparative Example were dried with hot air at 150°C for 3 hours using a hot air dryer, and then fed to a FANUC α30C injection molding machine (manufactured by FANUC). The cylinder temperature was set to the melting point of the liquid crystal polyester resin +40°C, the mold temperature was set to 90°C, the injection speed was set to 300mm / s, and the holding pressure was set to 70% of the peak pressure for 2 seconds, and the CPU socket shown in Figures 1 and 2 was injection molded in 10 shots under relatively high temperature and high pressure molding conditions. The usual molding conditions are a cylinder temperature of the melting point of the liquid crystal polyester resin +20°C, a mold temperature of 90°C, and an injection speed of 100mm / s. The average twist amount was measured for the obtained 10 CPU sockets. Here, the twist amount will be explained using Figure 3. Figure 3(a) shows a schematic diagram of the CPU socket shown in Figure 1 viewed in a planar direction from the gate (10) side, and S1 and S2 are set on both side surfaces as shown in Figures 3(a) and (b). At this time, the plane connecting S1 and S2 with a straight line is set as the reference plane L1. Next, as shown in Figure 3(b), when the CPU socket is twisted, a maximum displacement plane L2 that is parallel to L1 from the maximum displacement point is set, and the distance between L1 and L2 is measured. In Table 2, the average value of the twist amount of 10 CPU sockets is listed as "amount of twist after molding". Next, the 10 CPU sockets were placed in a hot air oven heated to 270°C for 3 minutes, and the amount of twist after heat treatment was measured in the same manner as described above. In Table 2, the average value of the twist amount of 10 CPU sockets after heat treatment is listed as "amount of twist after heat treatment". The smaller the value of the amount of twist, the better the resistance to twist during high-temperature and high-pressure molding.
[0089] (7) Molding stability The pellets of the liquid crystal polyester resin composition obtained in each Example and Comparative Example were dried with hot air at 150°C for 3 hours using a hot air dryer, and then subjected to a TR30EHA injection molding machine (manufactured by Sodick). Using a mold having a thickness unevenness structure in which the thickness of the flow part changes from 0.5mm to 0.1mm (the part with a thickness of 0.1mm has a bar flow shape with a width of 5mm and a length of 20mm), the cylinder temperature was set to the melting point of the liquid crystal polyester resin + 20°C, the mold temperature was set to 110°C, the injection speed was set to 200mm / s, and the peak pressure was set to 100MPa, and the flow length L1 (mm) of the 0.1mm thick part was measured. This flow length is the flow length at the plateau specific to the material. Next, the conditions were changed to a peak pressure of 150MPa, and 50 flow lengths L2 (mm) of the same part were measured. At this time, the better the molding stability of the material during high-pressure molding, the closer the difference between flow length L2 and flow length L1 (L2 - L1 (mm)) will be to 0 mm, but the less stable the material is, the higher the probability of abnormal filling occurring, where a difference of 3 mm or more occurs due to jetting or burrs. The number of pieces where L2 - L1 had a difference of 3 mm or more was counted to calculate the incidence of abnormal filling. This is shown in Table 2 as "Incidence rate of abnormal filling (%)." The lower the incidence rate, the better the molding stability during high-pressure molding.
[0090] [Table 2]
[0091] From the results in Table 2, it can be seen that a liquid crystal polyester resin composition containing a predetermined amount of fibrous filler (B) having a specific fiber length can provide a CPU socket having excellent metal fitting properties and torsion resistance during high-temperature, high-pressure molding. In addition, when the proportion of fibrous filler of 150 μm or more is small, it can be seen that a CPU socket having extremely excellent torsion resistance during high-temperature, high-pressure molding and excellent molding stability can be obtained. In addition, it can be seen that a liquid crystal polyester resin composition containing a predetermined amount of plate-shaped filler (C) can provide a CPU socket having excellent molding stability during high-pressure molding. [Explanation of symbols]
[0092] 10 CPU sockets 1 Gate location 2 Outer frame 3 Lattice structure 4 Pin insertion hole 5 Opening 6. Amount of twist S1 Socket Side S2 Opposite side of socket to S1 L1 reference plane L2 Maximum deformation surface [Industrial Applicability]
[0093] The CPU socket of the present invention has excellent metal fitting properties and excellent resistance to twisting during high-temperature, high-pressure molding, making it particularly suitable for electrical and electronic component applications that use such CPU sockets.
Claims
1. A CPU socket formed from a liquid crystal polyester resin composition containing 60 to 200 parts by weight of a fibrous filler (B) per 100 parts by weight of a liquid crystal polyester resin (A), wherein the fibrous filler (B) in the liquid crystal polyester resin composition satisfies the following requirement (α): (α): With respect to the fibrous filler (B) in the liquid crystal polyester resin composition, the fibrous filler (B) having a fiber length of 150 μm or more accounts for less than 20% of the total fibrous filler (B) by number, and the fibrous filler (B) having a fiber length of 20 μm or less accounts for less than 15% of the total fibrous filler (B) by number.
2. 2. The CPU socket according to claim 1, wherein the fibrous filler (B) having a fiber length of 150 [mu]m or more accounts for less than 6% of the total fibrous filler (B) in terms of number of fibers.
3. 2. The CPU socket according to claim 1, further comprising 1 to 100 parts by weight of a plate-like filler (C) per 100 parts by weight of the liquid crystal polyester resin (A).
4. 2. The CPU socket according to claim 1, wherein the liquid crystal polyester resin (A) is a liquid crystal polyester resin containing the following structural unit (I) and satisfies the following formula (a). 1≦[I]≦20...(a) ([I] indicates the content (mol %) of each structural unit (I) described below relative to 100 mol % of all structural units in the liquid crystal polyester resin.) 【Chemistry 1】
5. 2. The CPU socket according to claim 1, wherein the liquid crystal polyester resin (A) further contains the following structural unit (II) and is a liquid crystal polyester resin that satisfies the following formula (b): 0.1≦[II]≦10...(b) 【Chemistry 2】
6. 6. The CPU socket according to claim 1, wherein the thickness between the lattice structures in the lattice structure is 0.2 mm or less.
Citation Information
Patent Citations
Liquid crystal polyester composition
JP2012193343A
Planar connector
JP2012214652A
Composite resin composition and flat connector molded from same
WO2014050370A1